Probing Photocatalytic Characteristics of Sb-Doped TiO2 under Visible Light Irradiation. (6th April 2014) - Luo, Lingjing; Li, Tianfeng; Ran, Xia; Wang, Pan; Guo, Lijun
Abstract : Sb-doped TiO2 nanoparticle with varied dopant concentrations was synthesized using titanium tetrachloride (TiCl4 ) and antimony chloride (SbCl3 ) as the precursors. The properties of Sb-doped TiO2 nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), fluorescence spectrophotometer, and Uv-vis spectrophotometer. The absorption edge of TiO2 nanoparticles could be extended to visible region after doping with antimony, in contrast to the UV absorption of pure TiO2 . The results showed that the photocatalytic activity of Sb-doped TiO2 nanoparticles was much more active than pure TiO2 . The 0.1% Sb-doped TiO2 nanoparticles demonstrated the best photocatalytic activity which was better than that of the Degussa P25 under visible light irradiation using terephthalic acid as fluorescent probe. The effects of Sb dopant on the photocatalytic activity and the involved mechanism were extensively investigated in this work as well.